Innovation, social capital and regional policy: the case of the Communities First programme in Wales - David Pickernell (Regional Studies, Regional Science, 2018)
This paper analyses how and why different forms of social capital are associated with different forms of innovation within the Communities First programme in Wales. Quantitative analysis shows that the Communities First programme partnerships analysed in this research are supportive of building both bonding and bridging social capital. Different types of bonding social capital appear to be positively related with two of the three types of innovative activity; it is bridging social capital which is statistically more strongly related to innovation outcomes, with some types of bonding social capital actually negatively related to hidden innovation. Whilst social capital building should not be considered a panacea for increasing levels of innovative activity within policies such as the Communities First programme. The qualitative analysis reveals multiple ways in which the Communities First programme partnerships evaluated are actively encouraging the simultaneous formation of bonding and bridging social capital, with evidence of hidden innovation and in particular social innovation being simultaneously formed. It can be stated therefore, that regional policy aiming to develop non-traditional forms of innovation should more closely and explicitly reflect the relevance of building and maintaining particular types of bonding and especially bridging social capital.